Hindu Law’s Protection of Women’s Property Rights and Gender Equality - Deswal, Arjun (Innovative Research Thoughts, 2018)
Women have fought for their most basic rights in India and around the world from the beginning of civilization. Property rights are one example of these rights. It was expected in ancient Hindu custom that the daughter would marry and go to live with a new family. Therefore, only male Hindu family members would receive a portion in the event of a partition or property division. Only after marriage (stridhan) and on other auspicious occasions during public assemblies did women obtain property. Women were not allowed to own a portion of the property because they had no other source of income. Women have moved closer to equality with males over time. They are self-sufficient both materially and financially. In this case, laws would have to change to keep up with society. Consequently, a number of laws, such as the 1937 Hindu Women's Right to Property Act, the 1956 Hindu Succession Act (HSA), and the 2005 Hindu Succession (Amendment) Act, were passed in recent decades. A number of court rulings have also been made with the intention of resolving legal issues and determining the accurate interpretation. In this article, each of these laws and decisions has been carefully reviewed. In addition, there are still conflicting federal and state personal property laws pertaining to agricultural land inheritance. In this regard, there are regressive inheritance limitations in Delhi, Haryana, Uttar Pradesh, and Punjab. Indeed, married daughters are no longer considered major heirs in Uttar Pradesh as of 2016, and Haryana has repeatedly attempted to reverse the progressive privileges provided to women under the Hindu Succession Act. In several north Indian states, there is also grassroots opposition against land registration for women. Property rights and women's empowerment are thus still unresolved issues.